Branched ethylene-based polymer compositions and processes for making same
Patent Information
- Application Number
- JP2021530140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-30
- Filing Date
- 2019-11-26
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2039-11-26
Smart Images

Figure 0007638209000001 
Figure 0007638209000002 
Figure 0007638209000003
Abstract
Description
[Background technology]
[0001] The level of branching in low density polyethylene (LDPE) is primarily due to the reactor design and polymerization conditions used to make the LDPE. Branching agents have been used to increase the level of branching in LDPE. However, the process conditions required to achieve modified LDPE with high levels of branching often result in an end product with lower crystallinity and higher contents of low molecular weight extractable fractions. Thus, there is a need for modified LDPE that can be prepared under conditions that have high levels of branching and maintain good polymer properties. Summary of the Invention
[0002] The present disclosure provides a polymer composition. In one embodiment, an ethylene-based polymer composition is provided that is formed by reacting, via high pressure (100 MPa or higher) free radical polymerization, ethylene monomer with a mixture of hydrocarbon-based molecules, each of which contains three or more terminal alkene groups.
[0003] The present disclosure provides a process. In one embodiment, the process includes reacting ethylene monomer with a mixture of hydrocarbon-based molecules in a polymerization reactor under free radical polymerization conditions and at a pressure of 100 MPa or greater. Each of the hydrocarbon-based molecules includes three or more terminal alkene groups. The process includes forming an ethylene-based polymer composition. In a further embodiment, each of the hydrocarbon-based molecules has the structure I: [ka] In the formula, n is 3 to 160, and m is 0 to 50.
[0004] definition Any references to the Periodic Table of the Elements are to that as published in 1990-1991 by CRC Press, Inc. References to groups of elements in this table are to the new convention for numbering the groups.
[0005] For purposes of United States patent practice, the contents of any referenced patents, patent applications, or publications are incorporated by reference in their entirety (or the corresponding U.S. versions thereof are so incorporated by reference), particularly with respect to disclosure of definitions (to the extent that they do not conflict with any definitions specifically provided in this disclosure).
[0006] Numerical ranges disclosed herein include all values from and including the lower and upper limits, and when a range includes an explicit value (e.g., 1 or 2, or 3 to 5, or 6, or 7), any subrange between any two explicit values is included (e.g., the range 1 to 7 above includes subranges such as 1 to 2, 2 to 6, 5 to 7, 3 to 7, 5 to 6, etc.).
[0007] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0008] The term "composition" refers to a mixture of materials that make up the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0009] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional component, step, or procedure, whether specifically disclosed or not. For the avoidance of doubt, all compositions claimed through the use of the term "comprising" may include any additional additive, adjuvant, or compound, whether polymeric or not, unless stated to the contrary. In contrast, the term "consisting essentially of" excludes any other component, step, or procedure from the scope of any succeeding description, except those that are not essential to operability. The term "consisting of" also excludes any component, step, or procedure not specifically delineated or listed. The term "or" refers to the listed members individually as well as in any combination, unless otherwise stated. The use of the singular includes the use of the plural, and vice versa.
[0010] The term "polymer" or "polymeric material" as used herein refers to a polymer prepared by polymerizing monomers, whether of the same or different types, and provides in polymerized form the multiple and / or repeating "units" or "mer units" that make up the polymer. Thus, the general term polymer encompasses the term homopolymer, which is usually used to refer to a polymer prepared from only one type of monomer, and the term copolymer, which is usually used to refer to a polymer prepared from at least two types of monomers. It also encompasses all forms of copolymers, e.g., random, block, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" refer to the above-mentioned copolymers prepared from polymerizing ethylene or propylene, respectively, with one or more additional polymerizable α-olefin monomers. It is noted that while polymers are often referred to as "made of" one or more particular monomers, "based on" a particular monomer or monomer type, "containing" a particular monomer content, etc., in this context, the term "monomer" is understood to refer to the polymerized residue of a particular monomer, and not to the non-polymerized species. Generally, polymers are referred to herein in terms of "units" that are the polymerized form of the corresponding monomers.
[0011] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this application.
[0012] As used herein, the term "blend" or "polymer blend" refers to a mixture of two or more polymers. A blend may or may not be miscible (not phase separated at the molecular level). A blend may or may not be phase separated. A blend may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and other methods known in the art. A blend may be achieved by physically mixing two or more polymers at a macro level (e.g., melt blending resins or compounding) or at a micro level (e.g., co-molding in the same reactor).
[0013] As used herein, the term "ethylene / alpha-olefin copolymer" refers to a copolymer having greater than 50 mole percent polymerized ethylene monomer (based on the total amount of polymerizable monomers) and at least one alpha-olefin.
[0014] As used herein, the term "ethylene monomer" refers to a chemical unit having two carbon atoms with a double bond between them, and each carbon bonded to two hydrogen atoms, which chemical unit polymerizes with other such chemical units to form an ethylene-based polymer composition.
[0015] As used herein, the term "high density polyethylene" (or HDPE) refers to an ethylene-based polymer having a density of at least 0.94 g / cc, or at least 0.94 g / cc to 0.98 g / cc. HDPE has a melt index of 0.1 g / 10 min to 25 g / 10 min. HDPE is a polymer made from ethylene and one or more C3 to C6 20It may include an alpha olefin comonomer. The comonomer(s) may be linear or branched. Non-limiting examples of suitable comonomers include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, and 1-octene. HDPE can be prepared using either Ziegler-Natta, chromium-based, constrained geometry, or metallocene catalysts in slurry, gas phase, or solution reactors. Ethylene / C3-C 20 The α-ethylene olefin copolymers contain at least 50% by weight, or at least 70% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight of ethylene polymerized therein, in polymerized form.
[0016] As used herein, the term "hydrocarbon-based molecule" refers to a chemical moiety having only carbon and hydrogen atoms.
[0017] As used herein, the term “linear low density polyethylene” (or “LLDPE”) refers to a linear low density polyethylene having units derived from ethylene and at least one C3-C 10 LLDPE refers to linear ethylene / α-olefin copolymers containing a heterogeneous distribution of short chain branches, including units derived from α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by little, if any, long chain branching, in contrast to conventional LDPE. LLDPE has a density of less than 0.910 g / cc to 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN™ Linear Low Density Polyethylene Resins (available from The Dow Chemical Company), DOWLEX™ Polyethylene Resins (available from The Dow Chemical Company), and MARLEX™ Polyethylene (available from Chevron Phillips).
[0018] As used herein, the term "low density polyethylene" (or LDPE) refers to polyethylene having a density of 0.909 g / cc to less than 0.940 g / cc, or 0.917 g / cc to 0.930 g / cc, and long chain branching with a broad molecular weight distribution (MWD greater than 3.0).
[0019] The term "terminal alkene group" as used herein refers to a double bond between two carbon atoms in a polymer chain, one of the carbons in the double bond being a =CH2 group. Terminal double bonds are located at the end of the polymer chain and / or at the end of a branch of the polymer chain. The term "internal alkene group" as used herein refers to a 1,2-disubstituted carbon-carbon double bond, the carbon atoms being in a trans configuration (not a cis configuration). Internal alkene groups are located throughout the length of the polymer chain, but not at the end of the polymer chain or at the end of a branch along the polymer chain. Terminal and internal alkene groups are measured by infrared spectroscopy ("IR").
[0020] As used herein, the term "alkene content" refers to the number of terminal alkene groups plus the number of internal alkene groups present in a polymer chain per 1000 carbon atoms. Alkene content is measured by infrared spectroscopy ("IR").
[0021] Test Method Density is measured according to ASTM D792, Method B. Results are reported in grams per cubic centimeter (g / cc).
[0022] The term "GI200" as used herein refers to a gel index that includes all gels that are at least 200 microns in diameter. The degree of crosslinking of an ethylene-based polymer composition is measured by dissolving the composition in a solvent for a specified time and calculating the percent gel or unextractable components. The percent gel typically increases with increasing crosslinking levels. GI200 results are expressed in mm 2 / 24.6cm 3 will be reported.
[0023] G' value The term "G" value as used herein refers to the storage modulus of a material. The storage modulus is a measure of the stored energy or elastic response of a material. The term "loss modulus" (or G) as used herein is a measure of the dissipated energy of a material in response to stress. The samples used in the G' measurements were prepared from compression molded plaques. A piece of aluminum foil is placed on a backplate and a mold or die is placed on top of the backplate. 12 grams of resin is then placed in the die and a second piece of aluminum foil is placed above the resin and die. A second backplate is then placed on top of the aluminum foil. The entire ensemble is placed in a compression molding press run at the following conditions: 3 minutes at 150°C and 100 MPa, followed by 1 minute at 150°C and 150 MPa, followed by a "1.5 minute" quench cool to room temperature at 150 MPa. 25 mm disks are punched out of the compression molded plaques. The disks are 2.0 mm thick. Rheological measurements to determine G' are performed in a nitrogen environment at 170°C and 10% strain. The punched disk is placed between two "25 mm" parallel plates positioned in an ARES-1 (Rheometrics SC) rheometer oven. The oven is preheated for at least 30 minutes at 170 °C and the gap between the "25 mm" parallel plates is slowly reduced to 1.65 mm. The sample is then left in these conditions for exactly 5 minutes. The oven is then opened, the excess sample is carefully cut around the edges of the plates and the oven is closed. The storage modulus (G') and loss modulus (G") of the sample are measured via small amplitude oscillatory shear following a decreasing frequency sweep from 100 to 0.1 rad / s (if G" values below 500 Pa can be obtained at 0.1 rad / s) or from 100 to 0.01 rad / s. For each frequency sweep, one point per decade of frequency (logarithmic spacing) is used. Data were plotted on a log-log scale (G' (Y-axis) vs. G" (X-axis)). The Y-axis scale covers the range of 10-1000 Pa, while the X-axis scale covers the range of 100-1000 Pa. Using the Orchestrator software, select data in the region where G" is between 200 and 800 Pa (or using at least four data points).The data are fitted to a logarithmic polynomial model using the approximation Y=C1+C2 ln(x). Orchestrator software is used to determine G' at G" equal to 500 Pa by interpolation. G' and G" are reported in Pascals (Pa).
[0024] Hexane Extractables The term "hexane extractable" as used herein refers to the amount of hexane soluble material washed by hexane from the resulting polymer composition. Polymer pellets (from polymerization without further modification, 2.2 grams per press) are pressed to form a 3.0-4.0 mil thick film in a Carver press. The pellets are pressed in two stages. The melt phase is 3000 pounds for 3 minutes at 190°C. The compression phase is 40000 pounds for 3 minutes at 190°C. Non-residue gloves (PIP*CleanTeam*Cotton Lisle Examination Gloves, Part Number: 97-501) are worn to avoid contaminating the film with residual oils from the operator's hands. The film is die-cut into "1 inch x 1 inch" squares and weighed (2.5±0.05 g). The film is then extracted in a hexane container at "49.5±0.5°C" in a heated water bath for 2 hours. After 2 hours, the film is removed, rinsed with clean hexane, and dried in a vacuum oven (80±5°C) at full vacuum (ISOTEMP vacuum oven, Model 281A, 30 inches Hg) for 2 hours. The film is then placed in a desiccator and allowed to cool to room temperature for a minimum of 1 hour. The film is then reweighed and the amount of mass loss due to extraction in hexane is calculated. This method is based on 21 CFR §177.1520(d)(3)(ii) with one deviation from FDA protocol by using hexane instead of n-hexane. Extractable hexane is reported as weight %.
[0025] Melt Elasticity The term "melt elasticity" as used herein refers to the ability of a polymer to bend or become mobile from a static state when melted. Melt elasticity is measured using a D-MELT instrument (available from Goettfert GmbH Buchen, Germany). DMELT instruments include a commercially available plastometer and a digital balance incorporating a custom weighted sample. Samples for density measurements are prepared according to ASTM D1928. Samples are pressed at 190°C and 30,000 psi for 3 minutes, then pressed at (21°C) and 207 MPa for 1 minute. Measurements are performed within 1 hour of sample pressing using ASTM D792, Method B. For melt elasticity measurements, a weighted piston is used to extrude molten polymer strands from a standard plastometer (MP600 Extrusion Plastometer (Melt Indexer) System Installation & Operation Manual (#020011560), Tinius Olsen, 1065 Easton Road, Horsham, PA 19044-8009) barrel through a constant temperature (190 °C) standard ASTM D1238 MFR die (orifice height (8.000 ± 0.025 mm) and diameter (2.0955 ± 0.005 mm)). The extrudate is forced through a series of freely rotating rollers by a stepper motor (Stepper Motor and Controller Operation Manual, Oriental Motor USA Corporation, 2570W.237 thThe polymer strand is pulled over a roller driven by a tension roller mounted on a scale (Excellence Plus XP Precision Balance Operating Instructions, Mettler Toledo, 1900 Polaris Parkway, Columbus, Ohio 43240) platform, which is ramped over a range of speeds during the analysis. The force of the polymer strand resting on a tension roller mounted on a scale (Excellence Plus XP Precision Balance Operating Instructions, Mettler Toledo, 1900 Polaris Parkway, Columbus, Ohio 43240) platform is recorded by an integrated control computer. From linear regression of the acquired force data, the final reported value is determined based on a constant speed ratio (33.2) or strain (Ln[speed ratio]=3.5) of polymer strand speed to die exit speed. Melt elasticity is reported in units of centinewtons (cN).
[0026] Melt Index The term "melt index" as used herein refers to a measure of how easily a thermoplastic polymer flows when in a molten state. Melt index (I2) is measured according to ASTM D 1238, condition 190°C / 2.16 kg, and is reported in grams dissolved per 10 minutes (g / 10 min). I10 is measured according to ASTM D 1238, condition 190°C / 10 kg, and is reported in grams dissolved per 10 minutes (g / 10 min).
[0027] Melt Strength The term "melt strength" as used herein refers to a measure of the maximum tension that can be applied to a polymer in the molten state before the polymer breaks. Melt strength is measured at 190 °C using a Goettfert Rheotens 71.97 (Goettfert Inc., Rock Hill, SC). Molten samples (25-50 grams) are fed into a Goettfert Rheotester 2000 capillary rheometer with a flat entrance angle (180 degrees), length of 30 mm, diameter of 2 mm. The sample is fed into a barrel (L = 300 mm, diameter = 12 mm), compressed, and allowed to melt for 10 minutes, after which it is compressed at a constant piston speed of 0.265 mm / s (which is 38.2 s for a given die diameter). -1 The extrudate is extruded at a wall shear rate of 2.4 mm / s. The extrudate passes through a Rheoten wheel located 100 mm below the die exit and is 2 ) of accelerating speed. The force on the wheel (measured in centinewtons, cN) is recorded as a function of the wheel speed (mm / s). The sample is repeated at least twice until the two curves of force (cN) as a function of strand speed (mm / s) overlap. The curve that showed the highest speed at which the strand broke is then reported. Melt strength is reported in cN as the plateau force before the strand breaks.
[0028] Nuclear magnetic resonance ( 1 H NMR) The term "nuclear magnetic resonance" (or NMR) as used herein refers to the spectral analysis of a material or compound that reveals the elemental and structural composition of the material or compound. Samples for proton NMR were prepared using 0.1-0.2 g sample in 2.75 g of 30 / 70 wt / wt o-dichlorobenzene-d4 / perchloroethylene (ODCB-d4 / PCE) containing 0.001M Cr prepared in a 10 mm tube. Samples were heated at 115°C and vortexed to ensure homogeneity. Single pulse proton spectra were acquired on a Bruker AVANCE 400 MHz spectrometer equipped with a Bruker Dual DUL high temperature CryoProbe and a sample temperature of 120°C. PBD spectra were acquired with a ZG pulse P1=5us (~30°PW), 16 scans, AQ1.64s, D114S. The LDPE-PBD sample was run using a ZG pulse with 90° PW, 32 scans, AQ1.64s, D114s.
[0029] Gas Chromatography Analysis As used herein, the term "gas chromatography analysis" refers to a method for separating components of a compound by weight.
[0030] Aqueous extraction and preparation of headspace-solid phase microextraction (HS-SPME) Each film was prepared as described in the experimental section under "Extrusion Coating." Two grams (approximately 1 inch by 1 inch) of each sample (approximately 1.3 mils of polymer coated onto the release liner and removed to act as a free-standing film) were weighed into individual "20 mL" headspace vials and the vials were sealed. The vials with the films were equilibrated at 75° C. for 10 minutes and the headspace was extracted by SPME for analysis by gas chromatography using a quadrupole mass spectrometer (GC / qMS).
[0031] HS-SPME preparation Ten grams (approximately 1 inch x 1 inch) of each film was weighed into a 40 mL glass vial (I-Chem, high purity). The vial was completely filled with high purity water (ASTM Type I, reagent grade, Mill-Q Integral 3, 18.2 MΩ, <5 ppb TOC). The vial was sealed with a PTFE-lined cap and the film was extracted at 40°C for 48 hours. After 48 hours, the vial was removed from the oven and the contents were allowed to return to room temperature (approximately 4 hours). HS-SPME analysis was performed using 20 mL headspace vials. Each vial was primed with 3.5 g sodium sulfate (Sigma-Aldrich, ACS reagent grade, purified by heating in a 1050°F oven for 12 hours) and 10 grams of water extract (no film). The mixture was vigorously mixed and sonicated for 15 minutes to dissolve the sodium sulfate. The vials were then equilibrated at 75° C. for 10 min and the headspace was extracted by SPME for analysis by gas chromatography using a quadrupole mass spectrometer (GC / qMS).
[0032] GC / ODP / qMS analysis conditions The headspace in each vial was sampled by SPME and analyzed by GC / qMS. Quantification was performed using an external standard calibration procedure. Automated sample analysis was performed using a Gerstel Multipurpose Sampler (MPS), an Agilent 7890A gas chromatograph, and an Agilent 5975C Inert XL quadrupole mass spectrometer. The MPS was controlled using Gerstel's Maestro software. GC / qMS control and data collection were performed using Agilent's Chemstation software. The headspace of the water extract was sampled using a "2 cm x 50 / 30 μm" dialkenylbenzene / carboxyl / polydimethylsiloxane (Supleco) SPME fiber equilibrated with water at 75°C and stirred for 10 min. Components in the SPME fiber were desorbed with a split / splitless inlet at 250 °C and subsequently separated using an Agilent, VF-WAXms, 30mx250μmx0.5μm capillary column with an oven temperature program of 50 °C (held for 2 min) to 260 °C (held for 6 min), 15 °C / min, and an initial column flow of 2.0 mL / min of helium.
[0033] The samples were then comparatively ranked on a scale of 1 to 5 (1 indicating the least and 5 indicating the most) of oxygenated species (OS) or total volatile organic compounds (VOCs) detected within the material.
[0034] Gel Permeation Chromatography (GPC) The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5), and a 4-capillary viscometer (DV) coupled to a Precision Detectors (now Agilent Technologies) 2-angle laser light scattering (LS) detector model 2040. For all absolute light scattering measurements, a 15 degree angle is used for the measurements. The autosampler oven compartment was set at 160 degrees Celsius and the column compartment was set at 150 degrees Celsius. The columns used were four Agilent "Mixed A" 30 cm, 20 micron linear mixed bed columns. The chromatographic solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen injected. The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / min.
[0035] Calibration of the GPC column set was performed with at least 20 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10 intervals between each individual molecular weight. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights of 1,000,000 and above, and 0.05 grams in 50 milliliters of solvent for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were calculated according to (Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
number
[0036] A polynomial between third and fifth order was used to fit each polyethylene equivalent calibration point, with a small adjustment to A (approximately 0.375-0.440) to compensate for column resolution and band broadening effects, resulting in a homopolymer polyethylene standard with a molecular weight of 120,000.
[0037] Total plate counts for the GPC column set were performed with Eicosane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equation:
number
number
[0038] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software: 2 mg / ml sample target weight was used to add solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to a septa-capped vial that had been pre-sparged with nitrogen. Samples were dissolved at 160 degrees Celsius with "slow" shaking for 2 hours.
[0039] Calculations of Mn(GPC), Mw(GPC), and Mz(GPC) were based on GPC results using PolymerChar GPCOne™ software, the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4-6 using baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and the polyethylene equivalent molecular weights obtained from a narrow standard calibration curve at point (i) from Equation 1.
number
[0040] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly calibrate the pump flow rate (Flow (apparent)) of each sample by aligning the respective decane peak in the sample (RV (FM sample)) with the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is thus assumed to be related to a linear shift in flow rate (Flow (effective)). To facilitate the highest accuracy of the RV measurement of the flow marker peak, a least squares fitting routine is used to fit the peaks of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to determine the true peak position. After calibrating the system based on the flow marker peaks, the effective flow rate (relative to the narrow standard calibration) is calculated as in Equation 7. Processing of the flow marker peaks was performed by PolymerChar GPCOne™ software. An acceptable flow correction is that the effective flow rate should be within + / - 2% of the apparent flow rate. Flow (effective) = Flow (nominal) * (RV(FM calibrated) / RV(FM sample)) (Equation 7)
[0041] Triple Detector GPC (TDGPC) The chromatographic system, analytical conditions, column set, column calibration and calculation and distribution of conventional molecular weight moments were performed according to the methods described in Gel Permeation Chromatography (GPC).
[0042] With regard to the determination of the viscometer and light scattering detector offsets from the IR5 detector, a systematic approach for the determination of multi-detector offsets was performed in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatography Polym. Chpt 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym. Chpt 13, (1992)) using PolymerChar GPCOne™ software to optimize triple detector log (MW and IV) results from broad homopolymer polyethylene standards (Mw / Mn>3) to narrow standard column calibration results from a narrow standard calibration curve.
[0043] Absolute molecular weight data was obtained using PolymerChar GPCOne™ software in a manner consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injected concentration used in determining the molecular weight was obtained from the mass detector area and mass detector constant derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight (using GPCOne™) was obtained using the light scattering constant and the refractive index concentration coefficient, dn / dc, of 0.104, derived from one or more of the polyethylene standards described below. In general, the mass detector response (IR5) and light scattering constant (determined using GPCOne™) should be determined from a linear standard having a molecular weight greater than about 50,000 g / mole. Viscometer calibration (determined using GPCOne™) can be accomplished using the method described by the manufacturer, or alternatively, by using published values of suitable linear standards, such as Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology (NIST)). A viscometer constant (obtained using GPCOne™) is calculated that relates the specific viscosity area (DV) and injected mass for the calibration standard to its intrinsic viscosity. The chromatographic concentration is assumed to be low enough to preclude addressing the second viral coefficient effect (concentration effect on molecular weight).
[0044] Absolute weight average molecular weight (MW (Abs) ) is obtained by dividing (using GPCOne™) the light scattering (LS) area integrated chromatogram (factored by the light scattering constant) by the mass recovered from the mass constant and the mass detector (IR5) area. The molecular weight and intrinsic viscosity responses are linearly extrapolated (using GPCOne™) at the chromatographic end where the signal to noise is low. The other respective moments, Mn(Abs) and Mz (Abs) is calculated according to the following equations 8 and 9.
number
[0045] gpcBR branching index by triple detector GPC (3D-GPC) The gpcBR branching index is determined by first calibrating the light scattering, viscosity, and concentration detectors as described above. A baseline is then subtracted from the light scattering, viscometer, and concentration chromatograms. An integration window is then set to ensure integration of all of the low molecular weight retention volume ranges of the light scattering and viscometer chromatograms that indicate the presence of detectable polymer from the infrared (IR5) chromatogram. Linear polyethylene standards are then used to establish the Mark-Houwink constants for polyethylene and polystyrene. Once the constants are obtained, the two values are used to construct two linear reference conventional calibrations of polyethylene molecular weight and polyethylene intrinsic viscosity as a function of elution volume, as shown in equations (10) and (11). M PE =(K PS / K PE ) 1 / α PE + 1·MPS αPS+1 / αPE+1 (Formula 10) [η] PE =K PS M PS α+1 / M PE (Equation 11). The gpcBR branching index is a robust method for characterizing long chain branching as described in Yau, Wallace W., "Examples of Using 3D-GPC-TREF for Polyolefin Characterization," Macromol.Symp., 2007, 257, 29-45. The index avoids the "slice-by-slice" 3D-GPC calculations traditionally used in determining g' values and calculating branching frequencies in favor of the entire polymer detector area. From the 3D-GPC data, the bulk absolute weight average molecular weight (Mw, Abs) of the sample can be obtained by the light scattering (LS) detector using the peak area method. This method avoids the "slice-by-slice" ratio of the light scattering detector signal to the concentration detector signal, as required for traditional g' determination.
[0046] In 3D-GPC, the intrinsic viscosity of the sample was also obtained separately using equation (8). The area calculation in equations (5) and (8) offers greater precision since the overall sample area is much less susceptible to detector noise at the baseline and integration limits and to variations caused by the 3D-GPC settings. More importantly, the peak area calculation is not affected by the volume offset of the detector. Similarly, the sample intrinsic viscosity (IV) with high precision is obtained by the area method shown in equation (12).
number
[0047] To determine the gpcBR branching index, the light scattering elution area of the sample polymer is used to determine the molecular weight of the sample. The viscosity detector elution area for the sample polymer is used to determine the intrinsic viscosity (IV or [η]) of the sample. First, the molecular weight and intrinsic viscosity for a linear polyethylene standard, such as SRM1475a or equivalent, are determined using conventional calibrations for both molecular weight and intrinsic viscosity as a function of elution volume ("cc") per equations (2) and (13).
number
number
[0048] All statistics with a "cc" subscript are determined using the respective elution volume, the corresponding conventional calibration as described above, and the concentration (Ci). Values without subscripts are measurements based on the mass detector, LALLS, and viscometer area. PE The values of α and Log K are iteratively adjusted until the linear reference sample has a gpcBR measurement of zero. For example, the final values of α and Log K for determining the gpcBR in this particular case are 0.725 and -3.391, respectively, for polyethylene and 0.722 and -3.993, respectively, for polystyrene. These polyethylene coefficients were then entered into Equation 13.
[0049] Once the K and α values have been determined using the procedure described above, the procedure is repeated using a branched sample that is analyzed using the final Mark-Houwink constants obtained from the linear reference as the best fit "cc" calibration values.
[0050] The interpretation of gpcBR is straightforward. For linear polymers, the gpcBR calculated from equation (14) will be close to zero because the values measured by LS and viscometer will be close to the conventional calibration standards. For branched polymers, especially those with high levels of long chain branching, the gpcBR will be higher than zero. This is because the measured polymer molecular weight will be higher than the calculated Mw,cc and the calculated IVcc will be higher than the measured polymer IV. In effect, the gpcBR value represents the fractional change in IV due to the molecular size shrinkage effect as a result of polymer branching. A gpcBR value of 0.5 or 2.0 represents a molecular size shrinkage effect in IV at a level of 50% and 200%, respectively, for an equivalent weight of linear polymer molecules.
[0051] In these particular examples, the advantage of using gpcBR compared to traditional "g' index" and branching frequency calculations is due to the higher accuracy of gpcBR. All of the parameters used in the determination of the gpcBR index are obtained with high accuracy and are not adversely affected by the low 3D-GPC detector response at high molecular weights from the concentration detector. Errors in detector volume alignment also do not affect the accuracy of the gpcBR index determination.
[0052] Fourier transform infrared analysis Determination of the amount of terminal (vinyl) and internal (or trans) double bonds per 1000 carbons is performed by Fourier transform infrared analysis ("FTIR"). The sample films (approximately 250-300 microns thick) used for FTIR analysis are 190 ℃ Samples were compression molded by pressing approximately 0.5 g pellets in a Carver hydraulic press with heated platens set at 40° C. Terminal and internal alkene levels were measured following a procedure similar to that outlined in ASTM method D6248. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0053] The present disclosure provides an ethylene-based polymer composition that includes the polymerization product of ethylene monomer and a mixture of hydrocarbon-based molecules having three or more terminal alkene groups.
[0054] In one embodiment, the ethylene-based polymer composition is formed from a process involving high pressure (greater than 100 MPA) and free radical polymerization. Ethylene monomer and a mixture of hydrocarbon-based molecules having three or more terminal alkene groups are reacted together to form the ethylene-based polymer composition. The polymerization process is described in more detail below.
[0055] Hydrocarbon Molecules An ethylene-based polymer composition is a polymerization reaction product of ethylene and a hydrocarbon-based molecule having three or more terminal alkene groups. A hydrocarbon-based molecule has only carbon and hydrogen atoms and has three or more terminal alkene groups. As used herein, the term "hydrocarbon-based molecule containing three or more terminal alkene groups" (or interchangeably referred to as "hydrocarbon-based molecule") refers to a chemical moiety that is a polymer chain composed of only carbon and hydrogen atoms. The polymer chain is branched and has three or more ends, with an alkene group (i.e., a hydrocarbon double) bond at each end. As used herein, the term "mixture of hydrocarbon-based molecules" refers to two or more hydrocarbon-based molecules, at least two of which differ in structure, properties, and / or composition.
[0056] In one embodiment, the number of terminal alkene groups present in each of the hydrocarbon-based molecules is 3, or 5, or 7, or 8 to 17, or 18. In further embodiments, the number of terminal alkene groups present in each of the hydrocarbon-based molecules is 3 to 40, or 5 to 40, or 10 to 40, or 12 to 20. By way of example, a mixture of hydrocarbon-based molecules may include a first hydrocarbon-based molecule having three terminal alkene groups and a second hydrocarbon-based molecule having 12 terminal alkene groups.
[0057] In one embodiment, each of the hydrocarbon-based molecules in the mixture has the structure I, [ka] wherein n (the number of terminal alkene groups) is 3 to 160 and m (the number of internal alkene groups) is 0 to 50. In another embodiment, n is 3, or 5, or 10, or 20, or 30, or 40 and m is 0, or 10, or 20, or 40, or 50. In further embodiments, n is 3 to 160, or 5 to 100, or 9 to 40 and m is 0 to 30, or 1 to 20, or 2 to 10.
[0058] In one embodiment, the mixture of hydrocarbon-based molecules consists of two or more hydrocarbon-based molecules having structure I, [ka] In the formula, n is the number of terminal alkene groups, m is the number of internal alkene groups, and the average n content in the mixture of hydrocarbon-based molecules is 9 to 40, and the average m content is 1 to 10. The "average n content" is calculated by dividing the number average molecular weight (Mn) of the hydrocarbon-based molecules by the weight average molecular weight (Mw) and then multiplying by the fraction of terminal alkene groups. The "average m content" is calculated by dividing the number average molecular weight (Mn) of the hydrocarbon-based molecules by the weight average molecular weight (Mw) and then multiplying by the fraction of terminal alkene groups.
[0059] In one embodiment, the mixture of hydrocarbon-based molecules each have an average n content and an average m content (referring to Structure I of each hydrocarbon-based molecule, shown as "n / m") as follows: (9-40 / 1-10, or 12-38 / 2-8, or 13-37 / 2-6, or 15-35 / 2-6, or 19 / 3, or 33 / 5).
[0060] In one embodiment, the mixture of hydrocarbon-based molecules based on structure I has a molecular weight distribution of 1.2 to 20. In another embodiment, the mixture of hydrocarbon-based molecules based on structure I has a molecular weight distribution of 1.2, or 1.3, or 1.4 to 2, or 5 to 10 or 20. In further embodiments, the mixture of hydrocarbon-based molecules based on structure I has a molecular weight distribution of 1.2 to 20, or 1.3 to 10, or 1.5 to 5.
[0061] In one embodiment, each of the hydrocarbon-based molecules has the structure II: [ka] In the formula, n is 3 to 160, m is 0 to 50, x is 0 to 160, and y is 0 to 50. In another embodiment, n is 3, or 5, or 10, or 20, or 30, or 40, or 50-60, or 70-80, or 90, or 100, or 110, or 120, or 130, or 140, or 150, or 160; m is 0, or 10, or 20-30, or 40, or 50; x is 0, or 1, or 5, or 10, or 20, or 30, or 40, or 50-60, or 70-80, or 90, or 100, or 110, or 120, or 130, or 140, or 150, or 160; and y is 0, or 1, or 10, or 20-30, or 40, or 50. In further embodiments, n is from 3 to 160, or from 5 to 150, or from 9 to 140, or from 9 to 100, or from 9 to 50, or from 9 to 30; m is from 0 to 30, or from 1 to 20, or from 1 to 10; x is from 0 to 160, or from 1 to 50, or from 1 to 20, or from 1 to 10; and y is from 0 to 50, or from 1 to 20, or from 1 to 10.
[0062] The hydrocarbon-based molecules of Structure I and / or Structure II are hereinafter referred to interchangeably as "branching agents."
[0063] Notation in Structure I and Structure II [ka] is for the double bond Teto represents a transalkyl group.
[0064] In one embodiment, a mixture of hydrocarbon-based molecules having Structure I and / or Structure II with different molecular weights is used.
[0065] It is understood that the ethylene-based polymer composition can include (i) only Structure I, (ii) only Structure II, or (iii) a combination of Structure I and Structure II. It is understood that the term "ethylene-based polymer composition," as used herein, refers to a polymer that is the reaction product of ethylene with Structure I and / or Structure II.
[0066] In one embodiment, the ethylene based polymer composition comprises, in polymerized form, 95%, or 96%, or 97%, or 98% to 99%, or 99.5%, or 99.7%, or 99.9% ethylene, and the inverse of the mixture of hydrocarbon based molecules, or 5.0%, or 4.0%, or 3.0%, or 2.0% to 1.0%, or 0.5%, or 0.3%, or 0.1% of the mixture of hydrocarbon based molecules. The weight percentages are based on the total weight of the ethylene based polymer composition. In further embodiments, the ethylene-based polymer composition comprises from 95.0% to 99.9% by weight, or from 96% to 99.8% by weight, or from 98% to 99.8% by weight, of ethylene, and the mixture of hydrocarbon-based molecules is present in polymerized form in an amount from 5.0% to 0.1% by weight, or from 4.0% to 0.2% by weight, or from 2.0% to 0.2% by weight.
[0067] The ethylene based polymer composition has a density from 0.909 g / cc to 0.940 g / cc. In one embodiment, the ethylene based polymer composition has a density from 0.909 g / cc, or from 0.915 g / cc, or from 0.920 g / cc to 0.930 g / cc, or from 0.935 g / cc, or from 0.940 g / cc. In another embodiment, the ethylene based polymer composition has a density from 0.910 g / cc to 0.940 g / cc, or from 0.915 g / cc to 0.935 g / cc, or from 0.917 g / cc to 0.930 g / cc, or from 0.917 g / cc to 0.926 g / cc.
[0068] In one embodiment, the ethylene based polymer composition has a melt index (I2) from 0.10 g / 10 min to 200 g / 10 min. In another embodiment, the ethylene based polymer composition has a melt index from 0.1 g / 10 min, or 1.0 g / 10 min, or 5.0 g / 10 min, or 10 g / 10 min, or 20 g / 10 min, or 30 g / 10 min, or 40 g / 10 min, to 50 g / 10 min, or 60 g / 10 min, 70 g / 10 min, or 75 g / 10 min, or 80 g / 10 min, or 90 g / 10 min, or 100 g / 10 min. In further embodiments, the ethylene-based polymer composition has a melt index from 0.1 g / 10 min to 200 g / 10 min, or from 0.1 g / 10 min to 100 g / 10 min, or from 0.1 g / 10 min to 80 g / 10 min, or from 0.1 g / 10 min to 20 g / 10 min.
[0069] In one embodiment, the ethylene-based polymer composition has a melt index (I2) from 0.1 g / 10 min to 8.0 g / 10 min.
[0070] In one embodiment, the ethylene based polymer composition has an alkene content of 0.05 / 1000 carbons, or 0.15 / 1000 carbons, or 0.3 / 1000 carbons, or 0.4 / 1000 carbons, or from 1.0 / 1000 carbons, or 2.0 / 1000 carbons, or 3.0 / 1000 carbons. In one embodiment, the ethylene based polymer composition has an alkene content of 0.05 / 1000 carbons to 3.0 / 1000 carbons, or from 0.05 / 1000 carbons to 1 / 1000 carbons, or from 0.08 / 1000 carbons to 1 / 1000 carbons.
[0071] In one embodiment, the ethylene-based polymer composition has a melt elasticity from 0.1 cN to 100 cN and a melt index from 0.1 g / 10 min to 100 g / 10 min.
[0072] In one embodiment, the ethylene based polymer composition has a G' value greater than C+DLOG(I2), where C is 185 Pa and D is -90 PA / log(G / 10 min), where I2 is the melt index of the ethylene based polymer composition and Pa is in Pascals (N / m 2 ) and log(g / 10 min) is the logarithm of the melt index of the ethylene-based polymer composition.
[0073] In one embodiment, the ethylene-based polymer composition comprises 0 mm 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 In one embodiment, the ethylene-based polymer composition has a GI200 value of 0 mm 2 / 24.6cm 3 , or 0.05 mm 2 / 24.6cm 3 , or 0.3 mm 2 / 24.6cm 3 ~0.7mm 2 / 24.6cm 3 , 5mm 2 / 24.6cm 3 , or 20mm 2 / 24.6cm3 In a further embodiment, the ethylene-based polymer composition has a GI200 value of 0 mm 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 , or 0.05 mm 2 / 24.6cm 3 ~5mm 2 / 24.6cm 3 , or 0.3 mm 2 / 24.6cm 3 ~0.7mm 2 / 24.6cm 3 It has a GI200 value of
[0074] In one embodiment, the ethylene based polymer composition has a density from 0.900 g / cc to 0.940 g / cc and a melt index from 0.1 g / 10 min to 200 g / 10 min. In another embodiment, the ethylene based polymer composition has a density from 0.900 g / cc, or 0.910 g / cc, or 0.920 g / cc to 0.925 g / cc, or 0.930 g / cc, and a melt index from 0.1 g / 10 min, or 2.0 g / 10 min, or 3.0 g / 10 min to 9.0 g / 10 min, or 10 g / 10 min, or 100 g / 10 min. In further embodiments, the ethylene based polymer composition has a density from 0.900 g / cc to 0.940 g / cc, or from 0.910 g / cc to 0.930 g / cc, or from 0.917 g / cc to 0.925 g / cc, and a melt index from 0.1 g / 10 min to 200 g / 10 min, or from 0.1 g / 10 min to 100 g / 10 min, or from 0.1 g / 10 min to 20.0 g / 10 min.
[0075] In one embodiment, the ethylene-based polymer composition has one, some, or all of the following characteristics: an alkene content of 0.05 / 1000 carbons, or 0.15 / 1000 carbons, or 0.3 / 1000 carbons, or 0.4 / 1000 carbons, or ~1.0 / 1000 carbons, or 2.0 / 1000 carbons, or 3.0 / 1000 carbons, and / or (ii) a melt elasticity between 0.1 cN and 100 cN, and a melt index between 0.1 g / 10 min and 200 g / 10 min, and / or (iii) a G' value greater than or equal to C+Dlog(I2), where C is 185 Pa and D is -90 Pa / log(g / 10 min), and / or (iv) 0.05 mm 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 and / or (v) having a density of 0.909 g / cc to 0.940 g / cc.
[0076] In one embodiment, the ethylene-based polymer composition has a relationship of Mw(abs) to I2, where Mw(abs) is less than or equal to A+B(I2), where A is 2.65×10 5 g / mol, and B is -8.00 x 10 -3 (g / mole) / (dg / min) (hereinafter Equation A), and the ethylene-based polymer compositions have a G' vs. I2 relationship where G' is greater than or equal to )C+Dlog(I2), where C is 185 Pa and D is -90 Pa / log(g / 10 min) (hereinafter Equation B). In other words, the ethylene-based polymers of the invention have Mw(abs) values less than the value from Equation A and G' values greater than the value from Equation B.
[0077] In one embodiment, the ethylene-based polymer composition is a low density polyethylene (LDPE) comprising, in polymerized form, ethylene monomer and a mixture of hydrocarbon-based molecules.
[0078] The ethylene-based polymer composition of the present invention is produced via high pressure polymerization in a reactor. Without being bound to a particular theory, it is believed that the copolymerization of ethylene monomer with a mixture of hydrocarbon-based molecules can occur through multiple scenarios. Two possible scenarios are (i) reaction of the propagating polymer chain (PC) with the terminal alkene group of the hydrocarbon-based molecule followed by further propagation and termination, and (ii) reaction of the propagating polymer chain (PC) with the internal alkene group of the hydrocarbon-based molecule followed by further propagation and termination.
[0079] [ka] The resulting ethylene-based polymer composition (structure III) has a polyethylene chain (LDPE) directly attached to a hydrocarbon-based molecule. A single terminal alkene group or multiple terminal alkene groups can be attacked by propagating a polymer chain (PC) that leads to a single or multiple LDPEs attached to a hydrocarbon-based molecule. In one embodiment, two or more terminal alkene groups undergo copolymerization while the remaining terminal alkene groups remain unreacted.
[0080] [ka] The resulting ethylene-based polymer composition (structure IV) has two polyethylene chains attached to the hydrocarbon-based molecule at internal alkene group reaction points (within the "m" section of the hydrocarbon-based molecule) that combine to form LDPE units. A single internal alkene group or multiple internal alkene groups may be attacked by propagating a polymer chain (PC) that leads to a single or multiple LDPEs that copolymerize with the hydrocarbon-based molecule. In one embodiment, two or more internal alkene groups undergo reaction while the remaining internal alkene groups remain unreacted. A single internal and / or terminal alkene group or multiple internal and / or external alkene groups may be attacked by propagating a polymer chain (PC) that leads to a single or multiple LDPEs that copolymerize with the hydrocarbon-based molecule. In one embodiment, two or more alkene groups undergo reaction while the remaining internal alkene groups remain unreacted.
[0081] The end product of the in-reactor reaction and subsequent further propagation and termination of the growing polymer chain at the terminal alkene group (scenario I above) is different from the post-reactor grafting of terminal alkene groups, which is shown below. [ka]
[0082] In post-reaction grafting, the LDPE is attached to a hydrocarbon-based molecule at the reactive site of the terminal alkene group. A separate molecule, usually another LDPE, reacts with the intermediate product to form the resulting ethylene-based polymer composition.
[0083] The end product of the in-reactor reaction followed by further propagation and termination of the growing polymer chain with an internal alkene group (scenario ii above) is different from the post-reactor internal alkene grafting, which is shown below. [ka]
[0084] In a post-reaction internal alkene grafting reaction, the LDPE is attached to a hydrocarbon-based molecule at the reactive site of the internal alkene group. A separate molecule, typically another LDPE, reacts with the intermediate product to form the resulting ethylene-based polymer composition.
[0085] In one embodiment, the ethylene-based polymer composition has Structure III and / or Structure IV, as described above, and has one, some, or all of the following properties: (i) an alkene content of 0.05 / 1000 carbons, or 0.15 / 1000 carbons, or 0.3 / 1000 carbons, or 0.4 / 1000 carbons, or ∼1.0 / 1000 carbons, or 2.0 / 1000 carbons, or 3.0 / 1000 carbons, and / or (ii) a melt elasticity between 0.1 cN and 100 cN, and a melt index between 0.1 g / 10 min and 200 g / 10 min, and / or (iii) a G' value greater than or equal to C+Dlog(I2), where C is 185 Pa and D is -90 Pa / log(g / 10 min), and / or (iv) 0 mm 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 and / or (v) Density from 0.909 g / cc to 0.940 g / cc, and melt index from 0.1 g / 10 min to 200 g / 10 min.
[0086] In one embodiment, the ethylene based polymer composition has from 1.0 wt% to 5.0 wt% extractable hexane, based on the weight of the ethylene based polymer composition. In another embodiment, the ethylene based polymer composition has from 1.0 wt%, or 1.1 wt%, or 1.5 wt% to 2.6 wt%, or 3.5 wt%, or 5.0 wt% extractable hexane. In further embodiments, the ethylene based polymer composition has from 1.0 wt% to 4.5 wt%, or 1.1 wt% to 3.5 wt%, or 1.5 wt% to 2.6 wt% extractable hexane.
[0087] In one embodiment, the ethylene-based polymer composition comprises a blend component. A blend component is a polymer that does not contain a mixture of hydrocarbon-based molecules.
[0088] In one embodiment, the blend component is an ethylene-based polymer that does not contain a mixture of hydrocarbon-based molecules. Non-limiting examples of suitable ethylene-based polymers include ethylene / alpha-olefin copolymers, ethylene / C3-C8 alpha-olefin copolymers, ethylene / C4-C8 alpha-olefin copolymers, and copolymers of ethylene with one or more of the following comonomers: acrylates, (meth)acrylic acid, (meth)acrylic esters, carbon monoxide, maleic anhydride, vinyl acetate, vinyl propionate, monoesters of maleic acid, diesters of maleic acid, vinyltrialkoxysilanes, vinyltrialkylsilanes, and any combination thereof.
[0089] In one embodiment, the blend component is an ethylene-based polymer having a density of 0.890 g / cc, or 0.900 g / cc, or 0.905 g / cc, or 0.910 g / cc, or 0.915 g / cc, or 0.917 g / cc to 0.925 g / cc, or 0.930 g / cc, or 0.935 g / cc, or 0.940 g / cc, or 1.05 g / cc. In a further embodiment, the blend component ethylene-based polymer has a density of 0.900 g / cc to 0.940 g / cc, or 0.905 g / cc to 0.935 g / cc, or 0.910 g / cc to 0.930 g / cc, or 0.915 g / cc to 0.925 g / cc, or 0.917 g / cc to 0.925 g / cc.
[0090] In one embodiment, the blend components have a melt index (I2) of 0.1 to 200 g / 10 min.
[0091] In one embodiment, the blend component is high density polyethylene (HDPE).
[0092] In one embodiment, the blend component is linear low density polyethylene (LLDPE).
[0093] In one embodiment, the blend component is low density polyethylene (LDPE).
[0094] In another embodiment, the blend component is an ethylene / alpha-olefin copolymer. In a further embodiment, the alpha-olefin of the blend component is a C3-C8 alpha-olefin, or a C4-C8 alpha-olefin.
[0095] The present disclosure also provides articles comprising at least one component formed from a composition of one embodiment, or a combination of two or more embodiments, described herein.
[0096] In one embodiment, the article is a film coating.
[0097] In one embodiment, the article is a coating.
[0098] In one embodiment, the article is a film.
[0099] The ethylene-based polymer composition comprises a combination of two or more embodiments as described herein.
[0100] An article comprises a combination of two or more embodiments as described herein.
[0101] The present disclosure also provides a process for making the inventive ethylene-based polymer composition, which comprises reacting ethylene monomer in the presence of a mixture of hydrocarbon-based molecules having three or more terminal alkene groups in a polymerization reactor under free radical polymerization conditions and at a pressure greater than 100 MPA, which process comprises forming the inventive ethylene-based polymer composition.
[0102] In one embodiment, the polymerization is carried out in a reactor configuration comprising at least one tubular reactor or at least one autoclave reactor.
[0103] In one embodiment, the polymerization is carried out in a reactor configuration comprising at least one tubular reactor.
[0104] In one embodiment, the polymerization is carried out in a reactor configuration comprising at least one autoclave reactor.
[0105] In one embodiment, ethylene monomer is polymerized in the presence of at least 2 molar ppm (based on the amount of total monomers in the reaction feed) of a mixture of hydrocarbon-based molecules additive.
[0106] In one embodiment, the polymerization pressure is greater than or equal to 100 MPA.
[0107] In another embodiment, the polymerization is carried out at at least one polymerization pressure between 100 MPA and 360 MPA.
[0108] In a further embodiment, the polymerization is carried out at at least one temperature between 100°C and 380°C.
[0109] To produce highly branched ethylene-based polymer compositions, high pressure, free radical initiated polymerization processes are used. Two different high pressure, free radical initiated polymerization process types are known. In the first process type, a stirred autoclave reactor with one or more reaction zones is used. Autoclave reactors usually have several injection points for initiator or monomer feed, or both. In the second process type, a jacketed tube is used as the reactor, which has one or more reaction zones. Suitable, but not limited to, reactor lengths can be from 100 meters to 3000 meters (m), or from 1000 meters to 2000 meters. The beginning of the reaction zone is defined, with both types of reactors, typically by a side injection of either the initiator, ethylene, chain transfer agent (or telomer), comonomer(s), and combinations thereof. The high pressure process can be carried out in an autoclave reactor or a tubular reactor with one or more reaction zones, or in a combination of autoclave and tubular reactors, each containing one or more reaction zones.
[0110] In one embodiment, the initiator is injected prior to the reaction zone where free radical polymerization is to be induced.
[0111] In one embodiment, conventional chain transfer agents (CTAs) are used to control molecular weight.
[0112] In another embodiment, one or more conventional CTAs are added to the polymerization process of the present invention. Non-limiting examples of CTAs include propylene, isobutane, n-butane, 1-butene, methyl ethyl ketone, acetone, ethyl acetate, propionaldehyde, ISOPAR (ExxonMobil Chemical Co.), and isopropanol. In one embodiment, the amount of CTA used in the process is 0.01 weight percent to 10 weight percent of the total reaction mixture.
[0113] In one embodiment, the process includes a process recycle loop to improve conversion efficiency.
[0114] In one embodiment, the polymerization is carried out in a tubular reactor as described in International Patent Application PCT / US12 / 059469 (WO2013059042(A1)), filed October 10, 2012. This patent application describes a multi-zone reactor that describes alternative locations for feeding fresh ethylene to control the ethylene to CTA ratio and therefore the polymer properties. As described in International Patent Application PCT / US12 / 064284 (filed November 9, 2012) (WO2013078018(A2)), fresh ethylene monomer is added simultaneously at multiple locations to achieve the desired ethylene monomer to chain transfer ratio. Similarly, the addition of fresh CTA addition points is carefully selected to control the polymer properties. Fresh CTA is added simultaneously at multiple locations to achieve the desired CTA to ethylene monomer ratio. Similarly, the addition points and amount of fresh branching agent described in this application are controlled to control gel formation while maximizing the desired properties of improved melt strength and performance in the targeted application. Fresh branching agent is added simultaneously at multiple locations to achieve the desired branching agent to ethylene monomer ratio. The use of branching and / or coupling agents to broaden the molecular weight distribution and increase the melt strength of the polymer places additional requirements on the distribution of CTA and branching agent along the reactor system to achieve the desired change in product properties without or minimizing potential adverse effects such as gel formation, reactor fouling, process instability, and minimizing the amount of branching agent.
[0115] In one embodiment, the polymerization is carried out in at least one tubular reactor. In a multi-reactor system, an autoclave reactor precedes the tubular reactor. The addition points and amounts of fresh ethylene, fresh CTA, and fresh branching agent are controlled to achieve the desired ratios of CTA to ethylene monomer and branching agent to ethylene monomer in the feed to and / or in the reaction zone.
[0116] In one embodiment, the branching agent is fed directly to the reaction zone via a compression stage or directly to the feed to the reaction zone. The choice of reaction and / or feed point to the reaction zone depends on several factors, including, but not limited to, the solubility of the polyene in the pressurized ethylene and / or solvent, condensation of the polyene into the pressurized ethylene, and / or fouling due to premature polymerization of the branching agent in the preheater used to heat the reactor contents prior to initiator injection.
[0117] In one embodiment, the branching agent is fed directly to the reaction zone or directly to the feed to the reaction zone.
[0118] In one embodiment, the branching agent is added at the entrance to the reaction zone prior to or simultaneously with the addition of the free radical initiator, in another embodiment, the branching agent is added prior to the addition of the initiator to allow for good dispersion of the polyene.
[0119] In one embodiment, the branching agent is provided only to reaction zone 1.
[0120] In one embodiment, more branching agent by mass is added to reaction zone 1 compared to the amount (by mass) of polyene added to the subsequent reaction zone.
[0121] In one embodiment, the ethylene fed to the first reaction zone is from 10 percent to 100 percent of the total ethylene fed to the polymerization. In further embodiments, the ethylene fed to the first reaction zone is from 20 percent to 80 percent, further from 25 percent to 75 percent, further from 30 percent to 70 percent, and further from 40 percent to 60 percent of the total ethylene fed to the polymerization.
[0122] In one embodiment, the process is carried out in a reactor configuration comprising at least one tubular reactor. In a further embodiment, the maximum temperature in each reaction zone is between 150°C and 360°C, further between 170°C and 350°C, further between 200°C and 340°C.
[0123] In one embodiment, the polymerization pressure at the first inlet of the reactor is from 100 MPA to 360 MPa, further from 150 MPA to 340 MPa, further from 185 MPA to 320 MPa.
[0124] In one embodiment, the ratio of the "concentration of CTA in the feed to reaction zone i" to the "concentration of CTA in the feed added to reaction zone 1" is 1 or greater.
[0125] In one embodiment, the ratio of "concentration of CTA in the feed to reaction zone i" to "concentration of CTA in the feed added to reaction zone 1" is less than 1, even less than 0.8, even less than 0.6, even less than 0.4.
[0126] In one embodiment, the number of reaction zones ranges from 3-6.
[0127] Non-limiting examples of ethylene monomers used in the production of ethylene-based polymer compositions include purified ethylene obtained by removing polar components from a loop recycle stream or by using a reaction system configuration such that only fresh ethylene is used to make the polymers of the present invention. Further examples of ethylene monomers include ethylene monomer from the recycle loop.
[0128] In one embodiment, the ethylene-based polymer composition comprises ethylene monomer, a mixture of hydrocarbon-based molecules (structure I or structure II), and one or more comonomers, preferably one comonomer. Non-limiting examples of suitable comonomers include α-olefins, acrylates, carbon monoxide, methacrylates, (meth)acrylic acid, monoesters of maleic acid, diesters of maleic acid, anhydrides, vinyl acetate, vinyl propionate, vinyl trialkoxysilanes, vinyl trialkylsilanes, each having 20 or fewer carbon atoms. The α-olefin comonomers have 3 to 10 carbon atoms, or alternatively, the α-olefin comonomers have 4 to 8 carbon atoms. Exemplary α-olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene.
[0129] In one embodiment, the ethylene-based polymer composition comprises, as the only monomeric units, ethylene monomer and at least one hydrocarbon-based molecule (Structure I or Structure II).
[0130] Free Radical Initiators In one embodiment, a free radical initiator is used to prepare the ethylene-based polymer composition of the present invention. Non-limiting examples of organic peroxides include cyclic peroxides, diacyl peroxides, dialkyl peroxides, hydroperoxides, peroxycarbonates, peroxydicarbonates, peroxyesters, peroxyketals, t-butyl peroxypivalate, di-t-butyl peroxide, t-butyl peroxyacetate, t-butyl peroxy-2-hexanoate, and combinations thereof. In one embodiment, these organic peroxy initiators are used in an amount of 0.001% to 0.2% by weight based on the weight of the polymerizable monomer.
[0131] In one embodiment, an initiator is added to at least one reaction zone of the polymerization, the initiator having a "half-life temperature in 1 second" greater than 255°C or greater than 260°C.
[0132] In another embodiment, such initiators are used at a peak polymerization temperature of 320°C to 350°C.
[0133] In a further embodiment, the initiator comprises at least one peroxide group incorporated in the ring structure.Non-limiting examples of initiators include TRIGONOX301 (3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxanone) and TRIGONOX311 (3,3,5,7,7-pentamethyl-1,2,4-trioxepane) (both available from Akzo Nobel), and HMCH-4-AL (3,3,6,6,9,9-hexamethyl-1,2,4,5-tetroxanone) available from United Initiators.
[0134] In one embodiment, the tubular reactor configuration includes 3-5 reaction zones, fresh ethylene is fed to the front of the tubular reactor, recycled ethylene is fed to the side of the tubular reactor, fresh CTA is fed to the side of the tubular reactor, a mixture of hydrocarbon molecules is fed to the front of the tubular reactor, and a mixture of hydrocarbon molecules is fed directly after preheating of the tubular reactor.
[0135] Additives In one embodiment, the composition comprises one or more additives.Non-limiting examples of additives include stabilizers, plasticizers, antistatic agents, pigments, dyes, nucleating agents, fillers, slip agents, flame retardants, processing aids, smoke suppressants, viscosity control agents, and anti-blocking agents.The polymer composition may, for example, comprise less than 10 percent of the total weight of one or more additives based on the weight of the ethylene-based polymer composition.
[0136] In one embodiment, the ethylene-based polymer composition is treated with one or more stabilizers, for example, antioxidants such as IRGANOX 1010, IRGANOX 1076, and IRGAFOS 168. Generally, the ethylene-based polymer composition is treated with one or more stabilizers prior to extrusion or other melt processing.
[0137] In one embodiment, the ethylene-based polymer composition further comprises at least one other polymer in addition to the ethylene-based polymer of the present invention having a mixture of hydrocarbon-based molecules (structure I or structure II). Blends and mixtures of the ethylene-based polymer composition with other polymers can be prepared. Polymers suitable for blending with the polymer of the present invention include natural and synthetic polymers. Exemplary polymers for blending include propylene-based polymers, ethylene / alkene alcohol copolymers, polystyrene, impact-modified polystyrene, ABS, styrene / butadiene block copolymers and their hydrogenated derivatives (SBS and SEBS), and thermoplastic polyurethanes.
[0138] Other ethylene-based polymer compositions for blending with the present ethylene-based polymer compositions include homogeneous polymers such as olefin plastomers and elastomers (e.g., polymers available under the trade names AFFINITY Plastomers and ENGAGE Elastomers (The Dow Chemical Company) and EXACT (ExxonMobil Chemical Co.)); propylene-based copolymers (e.g., polymers available under the trade names VERSIFY Plastomers & Elastomers (The Dow Chemical Company) and VISTAMAXX (ExxonMobil Chemical Co.)) may also be useful as components of blends with the polymers of the present invention.
[0139] Purpose The ethylene-based polymer compositions of the present disclosure can be used in a variety of conventional thermoplastic manufacturing processes to produce useful articles, including, but not limited to, monolayer and multilayer films; molded articles, such as blow molded, injection molded, or rotational molded articles; coatings; fibers; woven fabrics, nonwoven fabrics, cables, pipes, greenhouse films, silo bag films, collated shrink films, food packaging films, or foams.
[0140] The ethylene-based polymer compositions can be used in a variety of films, including, but not limited to, transparent shrink films, collated shrink films, cast stretch films, silage films, stretch hoods, sealants, and diaper backsheets. Other suitable applications include, but are not limited to, wire and cable, gaskets and profiles, adhesives, footwear components, and automotive interior parts.
[0141] Applicants have unexpectedly discovered that a mixture of hydrocarbon-based molecules having either Structure I or Structure II used in the reactor, where n is greater than 3 (or n is greater than 5), resulting in an ethylene-based polymer composition with an increased number of branching points, results in a significant change in melt rheology. The higher branching levels result in reduced reactor fouling and gel formation of the ethylene-based polymer composition, as seen in the GPC, melt rheology data, and improved solubility of the ethylene-based polymer composition. The resulting ethylene-based polymer composition also has improved (reduced) taste and odor performance compared to some other polymer compositions modified with other types of branching agents, including, for example, PPG-AEMA. EXAMPLES
[0142] Commercially available reagents LDPE5004i, PG7004, PT7007, and PT7009 are each LDPE ethylene homopolymers produced in an autoclave reactor. Each is available from The Dow Chemical Company. Isopar E, Isopar H, and Isopar L are available from Exxon Chemicals.
[0143] Polybutadiene (Additive A: Nisso PB B-1000, Additive B: Nisso PB B-2000) was supplied by Nippon Soda Co., Ltd. The properties of these materials are shown in Table 1 below. [Table 1]
[0144] 1. Polymerization I: Autoclave Reactor Preparation of solutions Asymmetric diene comparison sample I: isoprenyl methacrylate (IPMA) shown below [ka] was charged to a 316 stainless steel delivery vessel and diluted with ethyl acetate to produce a final concentration of 7.8 wt %. The vessel was purged with nitrogen for 3 hours prior to use and kept under a 70 psig nitrogen pad.
[0145] Invention Example I: Additive A was charged to a 316 stainless steel supply vessel and diluted with Isopar™ E to produce a final concentration of 1.7 wt. %. The vessel was purged with nitrogen for 3 hours prior to use and kept under a 70 psig nitrogen pad during operation.
[0146] Various feed levels of this solution were introduced into the reactor to produce polymer samples. Additive B was added to the reactor in the same manner as Additive A.
[0147] Initiators: In a second 316 stainless steel supply vessel, the peroxide initiators tert-butyl peroxyacetate (TPA, a 20 wt % solution in ISOPAR™ H), and di-tert-butyl peroxide (DTBP, a 20 wt % solution in ISOPAR™ H) were combined with ISOPAR E to produce 1500 ppm by weight TPA and 415 ppm by weight DTBP (4:1 molar TPA / molar DTBP ratio). The vessel was padded and unpadded five times with 70 psig nitrogen prior to use and kept under the nitrogen pad during operation.
[0148] Ethylene was injected at 5500 gm / hr at 193 MPa pressure into a stirred (1600 rpm) 300 mL high pressure CSTR reactor and an external heating jacket was set to control the internal reactor temperature at 220°C. Propylene (CTA) was added to the ethylene stream at 6.2 MPa pressure and controlled at a rate to produce an end product MI of approximately 4 g / 10 min, then the mixture was compressed to 193 MPa and injected. A solution of the appropriate additive solution was pumped directly into the reactor at 193 MPa pressure via a high pressure pump. A peroxide initiator solution was added directly into the reactor at 193 MPA pressure through the side wall at a rate to control the ethylene conversion to near 12%.
[0149] The polymerization procedures for each experiment are detailed in Table 2 below. [Table 2]
[0150] The properties of the ethylene homopolymer produced in the autoclave reactor are provided in Table 3 below. [Table 3]
[0151] 2. Melting strength experiment Additional samples were prepared under the autoclave polymerization conditions of Polymerization I disclosed above. In particular, the feed rates of both Additive A and Additive B were varied while holding the melt index (MI) constant (at or near 4g / 10 min). Applicants discovered that increasing the amount of either Additive A or Additive B while holding the melt index constant increased the melt strength of the polymer. The results of the melt strength experiments are shown in Table 4 below. [Table 4]
[0152] 3. Extrusion Coating Each of the polymer compositions, control, comparative sample I, and inventive example I are subjected to extrusion coating, temperature, and shear to determine thermal stability and decomposition products. All coating experiments were performed on a Black-Clawson extrusion coating line. The extruder was equipped with a 3.5-inch, 30:1 L / D, 4:1 compression ratio single-flight screw and two helical Mattock mixing sections. The nominal die width of 91 cm (36 in) was decked (a metal dam at the die exit around the outer edge of the die to block flow in the die, used to reduce die width and reduce polymer flow out of the die) to an open die width of 61 cm (24 in). In extrusion coating, a deckle is a die insert that sets the coating width in a slot die coater or the extrusion width in an extrusion die. It works by restricting the flow as the material exits the die.
[0153] For extrusion coating evaluation, a constant 6 inch air gap was set for all resins. The die gap was set at 20 mils, but slight adjustments were required to maintain a constant coating thickness. The temperatures in each zone of the extruder were 177, 232, 288, and 316°C (die) (350, 450, 550, and 600°F (die)), respectively, leading to a target melt temperature of 605°F (318°C). The screw speed was 90 rpm, resulting in an output rate of 250 lb / hr. The line speed was 440 ft / min (fpm), resulting in a 1.3 mil coating on 50 lb / ream KRAFT paper (KRAFT paper was 24 inches wide, unbleached). Resins were coated onto release liners to obtain free-standing strips of polymer film for analytical testing (e.g., HS-SPME). Before the molten polymer curtain contacted the paper substrate, a 24 inch (61 cm) wide piece of silicone coated release liner was inserted between the polymer coating and the paper substrate to form a "polymer coating / release liner / kraft paper" configuration where the paper and release liner were not attached. The "polymer coating / release liner" sub-configuration was rolled and wrapped in food grade aluminum foil. The solidified polymer coating was peeled off the release liner for analytical testing.
[0154] The amount of neck-in (the difference between the actual coating width and the deckle width (61 cm)) was measured at line speeds of 440 feet per minute and 880 feet per minute (fpm), resulting in coating thicknesses of 1.3 mil and 0.65 mil, respectively. The extruder amperage and horsepower were recorded. The amount of backpressure for each polymer was also recorded, without changing the position of the backpressure valve. The drawdown is the line speed at which an edge defect in the polymer coating (typically the width of the polymer coating oscillating along the edge of the polymer coating) is noticed, or the melt curtain is completely torn away from the die. Reduction rate drawdown (RRDD) was measured for all resins at a screw speed of 45 rpm by increasing the line speed until an edge defect or web tear was noticed. The extrusion coating results are shown in Table 5 below. [Table 5] [Table 6]
[0155] As seen in Tables 3 and 5-6, Inventive Example I has excellent melt strength (MS), excellent thermal stability (low OS and VOC levels), and excellent extrusion coating properties. Note that Inventive Example I is more thermally stable during melt processing than Comparative Sample I, and does not decompose into chemical species during processing that produce pungent odors and can also impart bad odors and flavors to foods.
[0156] 4. Polymerization II: Tubular Reactor Comparative Sample A' and Comparative Sample B' The polymerization was carried out in a tubular reactor with three reaction zones. In each reaction zone, pressurized water was used to cool and / or heat the reaction medium by circulating this water through the reactor jacket. The inlet pressure was 222 MPa and the pressure drop across the tubular reactor system was about 30 MPa. Each reaction zone had one inlet and one outlet. Each inlet stream consisted of the outlet stream from the previous reaction zone and / or an added ethylene-rich feed stream. Unconverted ethylene and other gaseous components (in the reactor outlet) were recycled by high-pressure recycle and low-pressure recycle, compressed and distributed by booster, primary and hyper (secondary) compressors. Organic peroxides (tert-butylperoxy-2-ethylhexanoate and di-tert-butylperoxide) were fed to each reaction zone. Propionaldehyde (PA) was used as a chain transfer agent (CTA) and was present at each reaction zone inlet derived from the low-pressure and high-pressure recycle flows. Fresh PA was added only to the second and third reaction zones in ratios equal to 0.8 and 0.2, respectively. Fresh ethylene was directed to the first reaction zone.
[0157] After reaching the first peak temperature (maximum temperature) in reaction zone 1, the reaction medium was cooled using pressurized water. At the outlet of reaction zone 1, the reaction medium was further cooled by injecting cold ethylene-rich feed and the reaction was restarted by feeding the organic peroxide system. This process was repeated at the end of the second reaction zone to allow further polymerization in the third reaction zone. The polymer was extruded and pelletized (approximately 30 pellets per gram) using a single screw extruder at a melt temperature of approximately 230-250°C. The weight ratio of the ethylene-rich feed streams to the three reaction zones was 1.00:0.80:0.20. The internal process velocities were approximately 12.5, 9, and 11 m / sec in the first, second, and third reaction zones, respectively. Additional information can be found in Tables 7-10 below.
[0158] Invention Example 1' Polymerizations were carried out in a tubular reactor with three reaction zones as discussed above for Comparative Sample A'. All process conditions were the same as for Comparative Sample A', except for Inventive Example 1', where Additive A was added in the first zone. Amounts can be found in Table 8. Additional information can be found in Tables 7 and 9.
[0159] Invention Example 2' The polymerization was carried out in a tubular reactor having three reaction zones as discussed above for Inventive Example 1'. All process conditions were the same as Inventive Example 1', except that additional Additive A was fed to the first zone. Additional information can be found in Tables 7-9 below.
[0160] Invention Example 3' The polymerization was carried out in a tubular reactor with three reaction zones as discussed above for Inventive Example 1'. All process conditions were the same as Inventive Example 1', except that additional Additive A was fed to the first zone, and additional propionaldehyde (PA) was fed to adjust the melt index of the material. Additional information can be found in Tables 7-9 below. [Table 7] [Table 8] [Table 9]
[0161] As shown in Table 9, Comparative Samples (CS) PG7004, PT7007, PT7009 have higher Mw(abs) compared to their respective Formula A values, thereby indicating that Comparative Samples PG7004, PT7007, PT7009 are produced in an autoclave configuration. Comparative Samples A', B' and Inventive Examples 1', 2', and 3' each have Mw(abs) values less than the Formula A values, indicating polymerization in a tubular reactor configuration. PG7004, PT7007, PT7009, and Inventive Examples (IE) 1', 2', and 3' each have G' values higher than their respective values calculated from Formula B ("passing" Formula B), indicating greater and longer branching than would be possible in a tubular reactor without additives under the same temperature / pressure reactor conditions, as shown in Comparative Samples A', B' (without additive), which do not meet the G' requirements set forth in Formula B ("failing" Formula B). Inventive Examples 1', 2', 3' unexpectedly demonstrate the combination of enhanced branching (i.e., passing formula B) and production in a tubular reactor (i.e., passing formula A), thereby providing branched polymers in a low energy efficient production process.
[0162] The inventive examples demonstrate enhanced branching with the addition of an additive (Additive A) in multiple reactor types. The enhanced branching resulted in materials with superior melt elasticity and melt strength, which is advantageous in a variety of polymer applications, including extrusion coating. In particular, the use of the additive in a tubular reactor allows for melt strength in the inventive examples compared to materials produced in an autoclave reactor. The resulting ethylene-based polymer compositions also had improved (reduced) taste and odor performance compared to other polymer compositions modified with other types of branching agents.
[0163] It is expressly intended that the present disclosure is not limited to the embodiments and examples contained herein, but includes portions of the embodiments and modifications of these embodiments, including combinations of elements of different embodiments, as falling within the scope of the following claims. Examples of the invention of this application include the following: [1] An ethylene-based polymer composition formed by high pressure (above 100 MPa) free radical polymerization, the ethylene-based polymer composition being formed by reacting ethylene monomer with a mixture of hydrocarbon-based molecules, each hydrocarbon-based molecule containing three or more terminal alkene groups. [2] the hydrocarbon molecule has the structure I,
change
change
[10] The ethylene-based polymer composition according to any one of the above [1] to [9], wherein the ethylene-based polymer composition has an alkene content of 0.05 / 1000 carbons to 3.0 / 1000 carbons.
[11] The ethylene-based polymer composition, 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 The ethylene-based polymer composition according to any one of the above [1] to
[10] , having a GI200 value of.
[12] The ethylene-based polymer composition according to any one of the above [1] to
[11] , wherein the ethylene-based polymer composition has a density of 0.909 g / cc to 0.940 g / cc.
[13] The ethylene-based polymer composition according to any one of the above [1] to
[12] , wherein the ethylene-based polymer composition is a low-density polyethylene comprising, in polymerized form, an ethylene monomer and a mixture of the hydrocarbon-based molecules.
[14] The ethylene-based polymer composition according to any one of the above [1] to
[13] , further comprising a blend component, wherein the blend component does not contain the mixture of hydrocarbon-based molecules.
[15] An article comprising the composition according to any one of [1] to
[14] above.
[16] The article of
[15] above, wherein the article is selected from the group consisting of a film, a coating, a coating for a cable, a coating for a wire, and a coated sheet.
[17] A process comprising: reacting in a polymerization reactor under free radical polymerization conditions and at a pressure of 100 MPa or greater, ethylene monomer with a mixture of hydrocarbon-based molecules, each of the hydrocarbon-based molecules containing three or more terminal alkene groups; forming an ethylene-based polymer composition.
[18] Reacting ethylene monomer with a mixture of hydrocarbon-based molecules, each of the hydrocarbon-based molecules having the structure I:
change
[19] The process according to any one of
[17] to
[18] above, wherein the polymerization is carried out in a reactor configuration comprising at least one tubular reactor.
[20] The process according to any one of
[17] to
[18] above, wherein the polymerization is carried out in a reactor configuration comprising at least one autoclave reactor.
Claims
1. 1. An ethylene-based polymer composition formed by reacting ethylene monomer with polybutadiene, said polybutadiene having Structure I: 【Chemistry 1】 In the formula, the notation " 【Chemistry 2】 " is trans with respect to the double bond 2 represents an alkyl group, n is 3 to 160, and m is 0 to 50; the ethylene-based polymer composition comprises, in polymerized form, 95 wt.% to 99.98 wt.% ethylene and 0.02 wt.% to 5.0 wt.% of the polybutadiene, based on the total weight of the ethylene-based polymer composition; The following characteristics: (i) an alkene content of from 0.05 / 1000 carbons to 0.15 / 1000 carbons; (ii) a melt elasticity of 0.1 cN to 100 cN, and a melt index (I 2 ) (measured in grams / 10 minutes (g / 10 min) according to ASTM D 1238, condition 190° C. / 2.16 kg); (iii) C+Dlog(I 2 ) or more of storage modulus G' value (where G' is determined by rheological measurements in a nitrogen environment at 170° C. and 10% strain, C is 185 Pa, D is −90 Pa / log(g / 10 min), and I 2 is the melt index of the ethylene-based polymer composition, measured in grams / 10 minutes (g / 10 min) according to ASTM D 1238, Condition 190° C. / 2.16 kg; (iv) 0.05mm 2 / 24.6cm 3 ~20mm 2 / 24.6cm 3 (the GI200 value is a gel index that includes all gels that are at least 200 microns in diameter), and / or (v) a density from 0.909 g / cc to 0.940 g / cc; The ethylene-based polymer composition having one or more of:
2. 2. The ethylene-based polymer composition of claim 1, wherein the polybutadiene has a molecular weight distribution from 1.2 to 10.
3. 3. The ethylene-based polymer composition of claim 1 or 2, further comprising a blend component, said blend component being free of said polybutadiene.
4. An article comprising the composition of any one of claims 1 to 3.
5. The article of claim 4 , wherein the article is selected from the group consisting of a film and a coating.
6. 5. The article of claim 4, wherein the article is selected from the group consisting of a coating for cables, a coating for wires, and a coating for sheets.
7. A process comprising:
1. A process for reacting ethylene monomer with polybutadiene in a polymerization reactor under free radical polymerization conditions and at a pressure of 100 MPa or greater, wherein the polybutadiene has Structure I: 【Chemistry 3】 In the formula, the notation " 【Chemistry 4】 " is trans with respect to the double bond 2 alkyl, n is 3 to 160, and m is 0 to 50; forming an ethylene-based polymer composition; Including, the ethylene-based polymer composition comprises, in polymerized form, 95 to 99.98 weight percent ethylene and 0.02 to 5.0 weight percent of the polybutadiene, based on the total weight of the ethylene-based polymer composition.
8. 8. The process of claim 7, wherein the step of reacting ethylene monomer with polybutadiene is carried out in a reactor configuration comprising at least one tubular reactor.
9. 8. The process of claim 7, wherein the step of reacting ethylene monomer with polybutadiene is carried out in a reactor configuration comprising at least one autoclave reactor.
Citation Information
Patent Citations
Unsaturated ethylene-nonconjugated diene copolymers and their production by radical polymerization
JP1995500621A
Low-density ethylene polymer containing low molecular weight extracts
JP2015505330A
Ethylene-based polymers formed using asymmetric polyenes
JP2017502131A